Teacher Classroom Questioning Practice and Assessment Literacy: Case Studies of Four English Language Teachers in Chinese Universities - Jiang, Yan (Frontiers in Education, 2020)
This study examined classroom teacher questioning practice and explored how this process was affected by teacher assessment literacy and other mediating factors based on four case studies. Classroom observations were conducted to identify major patterns in teacher questioning practice and semi-structured interviews were carried out to probe the participants’ perception of classroom assessment, and how other factors, if there were any, along with teacher assessment literacy, impacted on teachers’ questioning practices. The finding showed that different teacher assessment literacies resulted in variability in teacher questioning patterns. It also illustrated that teacher day-to-day classroom practice involved a complex interplay among factors at the teacher personal, institutional, and socio-cultural levels. This study highlights the legitimacy of teacher questioning as a sub-construct of teacher assessment literacy, and calls for the establishment of a social and institutional culture aligning with assessment for learning principles.